Similarities and Differences in the Development of Laboratory Strains and Freshly Isolated Strains of Herpes Simplex Virus in HEp-2 Cells: Electron Microscopy - Schwartz, Jerome (1969)
HEp-2 cells infected with two laboratory strains (mP and MP) and two freshly isolated strains (F and G) of herpes simplex virus were fixed at intervals between 4 and 50 hr postinfection and sectioned, and were then examined with the electron microscope. These studies revealed the following. (i) All four strains caused identical segregation of nucleoli and aggregation of host chromosomes at the nuclear membrane. (ii) The development of MP virus could not be differentiated from that of its parent mP strain. (iii) There were quantitative differences between laboratory (mP) and freshly isolated (F) type 1 strains. Thus, cells infected with F contained numerous nuclear crystals of nucleocapsids and relatively few cytoplasmic structures containing enveloped nucleocapsids. Conversely, cells infected with mP or with MP virus contained numerous cytoplasmic structures with enveloped nucleocapsids and relatively few nuclear crystals of nucleocapsids. (iv) There were qualitative differences between type 2 strain (G) isolated from genital lesions and type 1 strains. Thus, cells infected with the G strain contain numerous filaments in nuclei and unenveloped and partially enveloped nucleocapsids in the cytoplasm. Of particular interest is the finding that cytoplasmic membranes in apposition to nucleocapsids were thickened and bent as if they were enveloping the particle. The significance of the qualitative differences in the development of the four strains is discussed.